2012
DOI: 10.2147/dddt.s34271
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment data is highly predictive of liver chemistry signals in clinical trials

Abstract: PurposeThe goal of this retrospective analysis was to assess how well predictive models could determine which patients would develop liver chemistry signals during clinical trials based on their pretreatment (baseline) information.Patients and methodsBased on data from 24 late-stage clinical trials, classification models were developed to predict liver chemistry outcomes using baseline information, which included demographics, medical history, concomitant medications, and baseline laboratory results.ResultsPre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…This is not surprising when one considers that “preexisting or acute liver disease” excludes qualification for Hy’s law, therefore subjects with the most severe abnormalities in HDCT did not qualify as meeting Hy’s law based on the attributions of their liver test abnormalities. Previous work has shown pretreatment bilirubin to be the most important predictor of meeting the criteria in Hy’s law (30) but most patients in our series who met Hy’s law criteria had normal bilirubin values at baseline. The few cases in our series that met Hy’s law criteria limit any meaningful conclusions, but the multifactorial nature of DILI makes it challenging to predict severe DILI with a single test.…”
Section: Discussioncontrasting
confidence: 53%
“…This is not surprising when one considers that “preexisting or acute liver disease” excludes qualification for Hy’s law, therefore subjects with the most severe abnormalities in HDCT did not qualify as meeting Hy’s law based on the attributions of their liver test abnormalities. Previous work has shown pretreatment bilirubin to be the most important predictor of meeting the criteria in Hy’s law (30) but most patients in our series who met Hy’s law criteria had normal bilirubin values at baseline. The few cases in our series that met Hy’s law criteria limit any meaningful conclusions, but the multifactorial nature of DILI makes it challenging to predict severe DILI with a single test.…”
Section: Discussioncontrasting
confidence: 53%
“…We identified ALT elevation recorded before MTX commencement as the strongest predictor for ALT elevation during MTX therapy. Some previous studies have reported ALT elevation at MTX commencement as a predictor for ALT elevations following the start of MTX therapy . By incorporating ALT for a longer pre‐treatment period, also including values antedating the onset of RA, we identified pre‐MTX ALT elevations in 20 of the 84 patients (24%) with ALT elevation, and all of them experienced recurrent ALT elevations during MTX therapy.…”
Section: Discussionmentioning
confidence: 93%